Mengembangkan UMKM Kicimpring Cipondok Melalui Desain, Kemasan Inovatif, Optimalisasi Branding Dan Penjualan Online - Hilda Nur Faidah; Imelda Dian Rahmasari; Shyfa Dwi; Silvia Zulfaizah; Sri Nur Alif; Tika Kartika6; Rizki Indrawan (CV. Armas Suan Sejahtera, 2025)
Micro, Small and Medium Enterprises (MSMEs) play an important role in local economic growth, but many still face obstacles in branding, packaging, and digital marketing. One of them is the Kicimpring MSME owned by Mrs. Rohaeni in Cipondok Village, Kadugede District, Kuningan Regency. This community service program aims to develop the MSME through innovative packaging design, branding optimization, and utilization of digital platforms for online sales. The activity was carried out from March to April 2025 with a participatory method and direct practice, which involved training in creating logos, product catalogs, product photos, and creating social media and marketplace accounts (Instagram, Shopee, and Linktree). The results of the activity showed a significant increase in product visualization and appeal, promotion effectiveness, and market reach. Product packaging became stronger, more attractive, and informative, while consistent digital branding improved the professional image of MSMEs. In conclusion, the participatory approach and intensive mentoring have proven to be able to significantly increase the competitiveness and independence of MSME actors. This program can be replicated in other MSMEs to encourage economic independence based on local potential.